Subarachnoid Fluid Lactate and Paraplegia after Descending Aorta Aneurysmectomy: Two Compared Case Reports - Enrico Giustiniano; Silvia Eleonora Malossini; Francesco Pellegrino; Franco Cancellieri (Case Reports in Anesthesiology)
We report a comparison of two cases regarding subjects who underwent thoracoabdominal aorta aneurysmectomy. During the procedure we monitored cerebrospinal fluid lactate concentration. One patient experienced postoperative paraplegia and his cerebrospinal fluid lactate concentration was much higher than that in the other case, whose postoperative outcome was uneventful. Consequently we consider that monitoring the lactate concentration in cerebrospinal fluid during thoracic aorta surgical procedures may be a helpful tool to predict the ischemic spine-cord injury allowing for trying to recover it precociously.